2021
DOI: 10.37398/jsr.2021.650213
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Antibacterial and Antifungal Activity of Various Leaves Extracts of Natural Plants Maesaindica (Wall) against Bacterial and Fungal Strains Causing Human Infection

Abstract: The indigenous plants are used as traditional medicinal plants from decades, which are useful in treatment of numerous contagious diseases. Medicinal plant of our community could be a wonderful origin of drugs which can cure these disease effortlessly .Active compound which are present in plants are responsible for the biological activities of the natural plants during the metabolism plant species. So, this investigation was focused to analyze the antimicrobial activity from leaves extract of medicinal plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Using herbal supplements has the goal of the recent research and studies related to it is bioactive compound which useful in medical therapy and as antifungal activity [37][38][39]. The result of these study revealed the activity of P-AgNO 3 NP as antifungal, the antifungal mechanism of P-AgNPs disrupted target species' transport systems, particularly ion efflux, and disrupted cellular activities such as metabolism and respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Using herbal supplements has the goal of the recent research and studies related to it is bioactive compound which useful in medical therapy and as antifungal activity [37][38][39]. The result of these study revealed the activity of P-AgNO 3 NP as antifungal, the antifungal mechanism of P-AgNPs disrupted target species' transport systems, particularly ion efflux, and disrupted cellular activities such as metabolism and respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to extensive study and the discovery of numerous drugs with both natural and chemical bases, the field of medicine has advanced significantly. Development of new and more affordable drugs from their natural habitat is greatly aided by the antifungal components found in herbal medicines [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%